The craft of information visualization readings and reflections - Bederson, Benjamin; Shneiderman, Ben. (Amsterdam ; London : Morgan Kaufmann, 2003)
The overall goal of research in Human-Computer Interaction (HCI) is to improve the experience of people using computers, making that experience more efficient and intuitive. The University of Maryland's Human-Computer Interaction Lab (HCIL) has repeatedly found that the most effective way to improve the human-computer experience is through the visual sense. Information visualization, the branch of research that studies the human-computer visual interface, has become a major theme during the past 10 years at HCIL. This book collects for the first time 38 of the key papers on information visualization.
Front Cover; The Craft of Information Visualization Readings and Reflections; Copyright Page; Contents; Preface; Acknowledgments; Introduction; Chapter 1. Database Discovery with Dynamic Queries; Chapter 2. Seeing the World Through Image Libraries; Chapter 3. Preserving Context with Zoomable User Interfaces; Chapter 4. The World's Information in Digital Libraries; Chapter 5. Making Sense of the World Wide Web; Chapter 6. Understanding Hierarchical Data; Chapter 7. Innovating the Interaction; Chapter 8. Theories for Understanding Information Visualization; Appendix A. Video Reports.
Includes bibliographical references and index.
Keywords: Information visualization; Human-computer interaction; Electronic books